Step by step - Wolkstein, Diane; Smith, Joseph A., (Joseph Anthony), 1936- (New York : Morrow, 1994)
A little ant and her friend enjoy a day together, dining on the nectar of a yellow flower, sailing on a leaf, and dancing in the rain.
Keywords: Fiction. -- Ants; Fiction. -- Insects; Fiction. -- Friendship